TEKNOLOGI PERTANIAN PRESISI UNTUK MENINGKATKAN EFISIENSI PRODUKSI PADI DI INDONESIA - Tulungen, Franky Reintje (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2024)
Precision Agriculture Technology (PAT) is increasingly becoming the main focus in improving rice production efficiency in Indonesia. This study aims to identify the benefits, challenges, and environmental impacts of the implementation of PAT in the context of rice farming in Indonesia. The research method used is qualitative by conducting a literature review of various related information sources. The study results show that PAT has great potential to improve rice production efficiency through advanced technologies such as soil sensors, drones, and smart irrigation systems. The main benefits of PAT include increased productivity, reduced production costs, and environmental conservation through the more efficient use of inputs. However, the implementation of PAT in Indonesia is still faced with challenges such as high costs, limited access, and a lack of awareness among farmers of the importance of this technology. In addition, there are also environmental impacts that need to be considered, such as the risk of soil and water contamination due to excessive use of pesticides and chemical fertilizers. Therefore, collaborative efforts are needed between the government, research institutions, the private sector, and farmers to overcome this challenge and maximize the benefits of PAT in improving the efficiency of rice production in Indonesia.